Chemical and Molecular Assessment of Heavy Metal Residues and Meat Species Mislabeling in Meat Products from Tikrit City, Iraq - M Thalij, Karkaz; A Salman, Fatma; A Jasm, Mohammed (Journal of Meat Science, 2026)
Ensuring the safety and authenticity of meat products is a key public health  priority, especially in areas with limited regulatory oversight. In Iraq, increasing  demand for processed meats has raised concerns about contamination with  toxic heavy metals and the mislabeling or adulteration of meat species. This  study aimed to evaluate both the chemical safety and biological authenticity of  commercially available meat products in Tikrit City markets by measuring heavy  metals (Pb, Cd, and Al) levels and verifying species identity using molecular  assays. A total of thirty meat samples, including commercial products and local  minced beef, were analyzed. Heavy metal concentrations were determined  after microwave digestion and inductively coupled plasma–mass spectrometry  (ICP-MS). DNA was extracted from all samples and amplified with species specific mitochondrial primers (456 bp universal, 271 bp bovine, and 225 bp  ovine), with agarose gel electrophoresis used to confirm the presence of bands.  Data were statistically analyzed with ANOVA at a significance level of p
Keywords: Meat varieties; heavy metals; PCR method; adulteration; authenticity; Iraqi markets